AHP Method System for Determining Road Repair Priorities in Dadimulyo Sub-District - Natasya, Tri Adetia; Handayani, Masitah; Rahayu, Elly (SAINTIS Publishing, 2025)
Improving road infrastructure plays a vital role in enhancing community mobility and fostering economic development within a region. In Dadimulyo Sub-district, one of the main challenges in infrastructure development lies in determining road repair priorities, especially under the constraints of limited budgets and available resources. This study proposes the development of a Decision Support System (DSS) utilizing the Analytical Hierarchy Process (AHP) method to facilitate more objective, transparent, and systematic decision-making. The AHP method enables the analysis of multiple criteria, such as current road conditions, traffic volume, accessibility, and community demand to assign weighted priorities for road repairs. The system is developed using the PHP programming language and MySQL as the database management system, ensuring both functionality and ease of data management. Based on the AHP calculations, Waterpas Road was identified as the highest-priority road for repair, receiving a final score of 0.227. The results of this study demonstrate that the integration of the AHP method into the decision-making process allows for more accurate prioritization and effective resource allocation. With this DSS, the government of Dadimulyo Sub-district is better equipped to optimize infrastructure planning, improve transparency, and ensure that limited budgets are directed toward areas with the greatest need and impact.